Pengaruh Kompensasi dan Kepuasan Kerja Terhadap Loyalitas Karyawan: Studi pada Karyawan Bank Majalengka - Asep Qustolani; Sabana Trisna Saputri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Employee loyalty is an important factor in supporting the sustainability and achievement of organizational goals, particularly in the banking sector, which demands high levels of professionalism, responsibility, and work commitment. However, the existence of issues related to the compensation system and the level of employee job satisfaction indicates the need for a more in-depth study of the factors influencing employee loyalty. This study aims to analyze the effect of compensation and job satisfaction on employee loyalty at Bank Majalengka, both partially and simultaneously. This research employs descriptive and verificative methods using a quantitative approach. The research data were obtained through the distribution of questionnaires to 99 employee respondents at Bank Majalengka. Data analysis was conducted using classical assumption tests, including normality tests, multicollinearity tests, heteroscedasticity tests using the Glejser method, and autocorrelation tests. Furthermore, the analysis was continued with model feasibility testing (F-test), multiple linear regression analysis, coefficient of determination (R²), and hypothesis testing (t-test). The results of the study show that compensation has a positive and significant effect on employee loyalty, while job satisfaction also has a positive and significant effect on employee loyalty.